Measuring Performance of Padang Panjang Public Hospital in Achieving Its Targets Using the Balanced Scorecard Method - Rahmi Hafianti; Yuniar Lestari; Erlinengsih Erlinengsih (Media Kesehatan Masyarakat Indonesia, 2022)
The Balanced Scorecard is widely used in various institutions, including hospitals because it can measure performance in a comprehensive, coherent, balanced, and measurable manner. Performance measurement at Padang Panjang Public Hospital so far focused on the financial aspect. This study aims to measure the performance of Padang Panjang Public Hospital in achieving its target with the Balanced Scorecard method. There are 14 indicators of performance that are measured in this study, namely economic ratio, efficiency ratio, and effectiveness ratio that describe performance from a financial perspective; customer satisfaction, complaint handling, customer retention, and market share that describe performance from a customer perspective; BOR (Bed Occupancy Rate), ALOS (Average Length of Stay), Bed Turn Over (BTO), and Turn Over Interval (TOI) which describe performance on the internal business process perspective and employee turnover, employee training, and employee productivity which describe performance from a learning and growth perspective. This is a mixed-method study, whereby the quantitative phase is followed by the qualitative phase. Quantitative data was taken and processed from hospital documents in 2018 and 2019. Each performance indicator is assessed by comparing it with its target. Interviews were conducted to get an explanation of the results obtained. Five of the fourteen performance indicator measurements have not reached the target, namely efficiency ratio, effectiveness ratio, BOR, employee training, and employee productivity. To improve performance, the hospital can focus on employee performance which will affect other performance indicators by providing education, training as well as employee job satisfaction.